Design and development of data logger with multiple SD cards for photovoltaic system / Najwa Nasuha Mahzan - Mahzan, Najwa Nasuha (2016)
Monitoring system has been a crucial process in any system which relates to the observing and examining the system in detail. The needs of having the monitoring system are sometimes to improve the system itself, to observe the vital changes that will affect the system or anything related, and to look for the system's performances for future reference. Thus, it is essential to have a good data logger which able to capture plenty of data from many sensors where all the data will be stored in huge data storage by means of having a bigger size of memory storage without being supervised frequently. A proposed data logger which implied a microcontroller of ATmega 2560 is introduced where it equips with many channels for taking data from stacks of sensors and definitely is having a gigantic size of memory to store the received data; two SD cards with the size of 4GB each are used throughout the project. The proposed data logger can be used in any systems which are related to electrical as well as in meteorological system provided that the sensors have electrical output that can be read directly or through signal conditioning. Based on the result testing from the proposed data logger, it has shown the low sampling rate in logging process where it could contribute much in logging stage under users' preferences, the low swapping time between two SD cards as low as 1.40 ms when error occurred which can activate the second memory storage immediately without hassle, and lastly the workability of the data logger performances via its characteristics.